Improving Science Learning Outcomes on Human Blood Circulatory System Material Through Experimentation Method for Fifth Grade Students - Serli Santika; Yusni Arni; Putri Malasari; Lala Dwi Putri; Yesi Tahni (Pusdikra-Publishing.com, 2024)
This research was motivated by the low science learning outcomes of class V students at SD Negeri 6 Palembang. The aim of this research is to improve the science learning outcomes of fifth grade students at SD Negeri 6 Palembang on the circulatory system material. The learning method that researchers used was the experimental method. This type of research is class action. (PTK) This is carried out in 2 cycles through 4 stages, namely: 1) planning, 2) implementation, 3) Observation, 4) Reflection. The methods used in collecting data are observation, documentation and tests. The research results showed that learning outcomes using the experimental method from cycle I to cycle II experienced a significant increase. The observation results show that the average value in the pre-cycle, that's not what it's about, was 61.67, increasing in cycle 1 to 76.32 in the active category, then in cycle 2 it increased to an average of 87.79, so that from cycle I and cycle II 2 there was an increase of 73. .53%. This shows that the use of experimental methods is able to improve student learning outcomes in science subjects on the subject of the circulatory system.